Environmental Education (Eco-Islam) in the Islamic Religious Education Curriculum: A Literature Review of Integration and Its Implications - Tohawi, Agus; Indramawan, Anik; Anwar, Muhamad Ali; Mastur, Mastur; Fuad, Nur; Utomo, Achmad Fauza Setyo; Rahma, Leily Vidya (West Science Islamic Studies, 2024)
The global environmental crisis demands a solution approach from various perspectives, including religion. Islam, with its comprehensive teachings (Eco-Islam), offers environmental conservation values ​​and ethics. The integration of these values ​​into the Islamic Religious Education (PAI) Curriculum has strategic potential to form environmentally friendly awareness and behavior from an early age. This research aims to review and synthesize literature findings regarding the Eco-Islam based environmental education integration model in the PAI curriculum, as well as analyze the implications of this integration. The literature review identified several effective integration models, such as: (1) Thematic integration into material on Aqidah, Akhlak, Fiqh, and Islamic Cultural History; (2) Environmentally based project approach; and (3) Development of special modules. The results of the study also show that this integration has positive implications for increasing ecological awareness, changing student behavior, and strengthening characters who are responsible for nature. The integration of Environmental Education (Eco-Islam) into the PAI curriculum is not only relevant but also urgent. This approach has the potential to create a generation of Muslims who are not only spiritually religious but also responsive to environmental issues. Commitment is needed from curriculum developers, educators and policy makers to realize systematic and sustainable integration.